Knowledge Mapping of Enterprise Network Research in China: A Visual Analysis Using CiteSpace - Yang, Wancheng; Wang, Shaofeng; Chen, Chen; Leung, Ho Hon; Zeng, Qi; Su, Xin (Frontiers in Psychology, 2022)
Enterprise Network (EN) has increasingly gained popularity in academia. Over the past few decades, a substantial amount of EN studies have been published in China. Drawing upon a sample of 603 papers retrieved from the Chinese Social Sciences Citation Index database (CSSCI) between 1998 and 2020, this study aims to delve into the status quo, knowledge base, research focus, and evolutionary trends of EN research in China. A multifaceted bibliometric analysis was performed using CiteSpace. The findings mainly indicate that the research on EN in China has a clear development context, and the research content gradually changes from macro to micro. In addition to foreign Social Network theories, the research results of domestic scholars have become the basic knowledge in this field. The research includes these topics: the conceptualization of EN, EN as indicators of enterprise development, EN’s impact on start-ups, mechanisms of EN’s effect and governance of EN. The potential direction for future research has been identified as the integration between EN and other forms of networks, and the structure of EN.